An overmassive dark halo around an ultra-diffuse galaxy in the virgo cluster - Beasley, Michael A.; Martínez-Delgado, David (Arxiv, 2016)
Ultra diffuse galaxies (UDGs) have the sizes of giant galaxies but the luminosities of dwarfs. A key to understanding their origins comes from their total masses, but their low surface brightnesses ($μ(V) ≥$ 25.0) generally prohibit dynamical studies. Here we report the first such measurements for a UDG (VCC~1287 in the Virgo cluster), based on its globular cluster system dynamics and size. From 7 GCs we measure a mean systemic velocity $v_{\rm sys}$ = 1071$^{+14}_{-15}$ km/s, thereby confirming a Virgo-cluster association. We measure a velocity dispersion of 33$^{+16}_{-10}$ km/s within 8.1 kpc, corresponding to an enclosed mass of $(4.5 ± 2.8)×10^{9}$ $M_{\odot}$ and a
Gesehen am 08.11.2017